Migration from the Philippines, 1975-1995 an annotated bibliography - Yukawa, Joyce (Quezon City Scalabrini Migration Center, 1996)
It holds a substantial collection of literature on Asian migration.
"This book is divided into two parts, General Studies and Regional and Country Studies. It also has author index and subject index."
Keywords: Migrant labor -- Bibliography; Filipinos -- Employment -- Foreign countries -- Bibliography; Philippines -- Emigration and immigration -- Government policy -- Bibliography